Relationships between energy cost, swimming velocity and speed fluctuation in elite butterfliers - Barbosa, Tiago M. (2011)
The purpose of this study was to analyse the relationships between the total energy expenditure (tot), the energy cost (EC), the intra-cycle variation of the horizontal velocity of displacement of centre of mass (dv) and the mean swimming velocity (v) in elite butterfliers.